2022
DOI: 10.3389/fimmu.2022.818736
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation as an Important Regulator of Antibody Function

Abstract: Antibodies play a critical role in linking the adaptive immune response to the innate immune system. In humans, antibodies are categorized into five classes, IgG, IgM, IgA, IgE, and IgD, based on constant region sequence, structure, and tropism. In serum, IgG is the most abundant antibody, comprising 75% of antibodies in circulation, followed by IgA at 15%, IgM at 10%, and IgD and IgE are the least abundant. All human antibody classes are post-translationally modified by sugars. The resulting glycans take on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 191 publications
(207 reference statements)
0
38
0
Order By: Relevance
“…2 ). For example, the human IgG1 Fc region is glycosylated at the conserved Asn297 residue, and IgG1 antibodies in healthy adults are typically characterized by high levels of fucosylation (85–95%), intermediate levels of galactosylation (25–40%), low levels of bisection (5–15%) and low levels of sialylation (2–15%) 123 , 124 . The glycosylation pattern of IgG1 directly influences its affinity for FcγR.…”
Section: Features Of Antibodies To Sars-cov-2mentioning
confidence: 99%
“…2 ). For example, the human IgG1 Fc region is glycosylated at the conserved Asn297 residue, and IgG1 antibodies in healthy adults are typically characterized by high levels of fucosylation (85–95%), intermediate levels of galactosylation (25–40%), low levels of bisection (5–15%) and low levels of sialylation (2–15%) 123 , 124 . The glycosylation pattern of IgG1 directly influences its affinity for FcγR.…”
Section: Features Of Antibodies To Sars-cov-2mentioning
confidence: 99%
“…We found that serum IgG of LEPAD patients had a significantly higher binding level of SNA (preferred sialic acid), ConA (preferred mannose), and PSA (preferred fucose) compared to CAS, with results of SNA and ConA confirmed by lectin blot analysis. Sialylation of the IgG Fc domain has been found to impair the complement-dependent cytotoxicity (CDC) effect [ 21 ], a reduction of which has been observed during inflammation and autoimmune disease flares [ 22 ]. It has been reported that loss of sialic acid might contribute to ischemic stroke [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The removal of glycosylation abolishes FcR binding and antibody-dependent cellular cytotoxicity (ADCC). In particular, sialylation in the Fc domain elongates the half-life in serum [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%